From the groma to the city: new data on the urban planning of Civita Musarna (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2024)
Grazie alle indagini archeologiche che hanno restituito il layout urbanistico della città in diacronia, il contributo si concentra sull'analisi della città etrusca di Civita Musarna quale piattaforma per lo studio della gromatica urbana e delle misure adottate nell’area. Lo studio si propone di delineare il più probabile percorso di tracciamento gromatico di Civita Musarna applicando un metodo di analisi retrospettiva, dove ogni fase del processo di ricerca viene considerata e discussa in relazione agli altri risultati. Così, l’indagine non solo contribuisce alla comprensione della pianificazione urbana etrusca, ma offre anche spunti per ulteriori studi sulle pratiche agrimensoria e urbanistica antiche. This contribution focuses on the analysis of the Etruscan city of Civita Musarna as a foundation for understanding urban gromatics and documenting measures adopted in the area, based on results of recent archaeological investigations that shed light on the evolution of the city’s urban layout. The study aims to outline the most probable path of gromatic tracing of Civita Musarna by applying a retrospective analysis method, where each stage of the research process is considered and discussed in relation to other findings. This investigation not only contributes to the understanding of Etruscan town planning, but also offers insights for further studies on ancient land surveying and town planning practices.
Keywords: Etruscan civilisation; Civita Musarna; town planning; land planning; groma